The Evaluation Of The Toxic Effect Of Paraquat And Its Mechanism Of Action On Reproductive System Of Male Rats [RA1242.P34 A636 2007 f rb]. - Md. Zain, Anuar (2007)
Paraquat® - PQ (1,1’ – dimethyl 4,4’ – bipyridillium dichloride) is a nonselective contact herbicide. Its herbicidal and toxicological properties are dependent on the ability of the parent cation to undergo a single electron addition to form a free radical.